Publiek werk : 1995-2000 vijf jaar praktijkbureau beeldende kunstopdrachten. (Amsterdam : SKOR, 2001)
Acconci Studio ; Bade, David ; Bastiaans, Christiaan ; Buy, Tilly ; Cattelan, Maurizio ; Claassen, Tom ; François, Michel ; Groenewoud, Gerard ; Holleman, Arnoud ; Höller, Carsten ; Jacobs, Henri ; Jongstra, Atte ; Kawamata, Tadashi ; Killaars, Fransje ; Kinoshita, Suchan ; Koelewijn, Job ; Konrad, Aglaia ; Langenberg, Sjaak ; van Lieshout, Erik ; Litgeringen, Ellen ; Mark, Arno Van der ; Mik, Aernout ; Mistiaen, Carlo ; Muñoz, Juan ; One Architecture ; Paraponaris, Hervé ; Post, Liza May ; de Rijke, Jeroen de & Rooij, Willem ; Rizzi, Mario ; Robaard, Joke ; Ruppersberg, Allen ; Scholte, Rob ; Seyferth, Christoph ; Starr, Georgina ; Sterren, Gé-Karel Van Der ; Strik, Berend ; Tempo, Frazione Di ; Tuinder, Dick ; Villevoye, Roy ; de Vries, Herman
boek